Polarization method and device for improving mechanical quality factor of ion-doped ferroelectric crystal
By combining the AC electric field and a uniform light field with a crystal band gap energy, the defective dipoles in the ion-doped ferroelectric crystal are activated and regulated, and the problem of low efficiency in the improvement of mechanical quality factor in the prior art is solved, and a significant improvement of mechanical quality factor is achieved.
Patent Information
- Application Number
- CN202411903624.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-08
AI Technical Summary
The existing polarization methods have problems of inefficiency and difficulty in adapting to lead-free ferroelectric transistors in improving the mechanical quality factor of ion-doped ferroelectric transistors.
The light AC polarization method combining an alternating current field and a uniform light field higher than the band gap energy of the crystal is used to activate the defective dipoles in the crystal and oriented in the polarization direction, thereby improving the mechanical quality factor.
Through the light AC polarization method, the mechanical quality factor of ion-doped ferroelectric crystals is significantly improved, which is several percentages higher than the traditional method, and is suitable for different types of ion-doped ferroelectric transistors.
Smart Images

Figure CN119776995A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of performance improvement of ion-doped ferroelectric crystals, and in particular to a polarization method and device for improving the mechanical quality factor of ion-doped ferroelectric crystals. Background Art
[0002] Ferroelectric crystals usually require electric field polarization to regulate the orientation of the domain structure to obtain high application performance. The doped ions in ion-doped ferroelectric crystals will introduce defect dipoles. When the defect dipoles are aligned with the domain structure orientation, the pinning effect provided by the defect dipoles can limit the movement of the domain wall and thus improve the mechanical quality factor of the crystal.
[0003] The existing polarization methods face some defects. The high-temperature DC polarization method usually applies a DC electric field several times the coercive field of the ferroelectric crystal at high temperature for polarization. The disadvantage is that the DC electric field needs to be applied continuously for several hours and the high temperature environment needs to be maintained, which takes a long time. The AC polarization method usually applies dozens of cycles of AC electric field to the crystal at room temperature to orient the domain structure along the final electric field direction. The maximum value of the electric field is several times the coercive field of the crystal, and the frequency is selected from 1 Hz to tens of Hz according to different crystal characteristics. The disadvantage is that it is currently usually used in PT-based relaxor ferroelectric single crystals, and it is difficult to achieve high polarization quality for lead-free ferroelectric crystals.
[0004] Patent CN 117468096 B discloses a high-stability light field assisted polarization device and method for ion-doped ferroelectric crystals, which can improve the polarization effect compared with the present application, but the present application can also significantly improve the mechanical quality factor.
[0005] Light fields that exceed the band gap energy of the crystal can activate defects inside the crystal, putting it in an unstable state. Compared with DC electric field polarization, the energy required for defect movement in the crystal under the action of AC electric field is lower. Therefore, by combining AC electric field and light, the defect dipoles in the crystal are more easily reoriented along the direction of the external electric field, so that the defect dipoles that were originally randomly oriented and had a macroscopic orientation of 0 have a macroscopic orientation along the direction of the external electric field, so that after light AC polarization, a crystal with the defect dipole orientation consistent with the spontaneous polarization orientation is obtained, and a photoinduced internal field is formed at the same time. The pinning effect of the defect dipole will limit the movement of the domain wall, thereby improving the mechanical quality factor of the crystal. The defect dipole orientation is consistent with the spontaneous polarization orientation, the internal state of the crystal is more stable, and has a larger mechanical quality factor.
[0006] Defect dipoles are usually difficult to be controlled by electric fields. Using light field irradiation with energy higher than the crystal band gap can enhance the activity of defects and cause defect dipoles to be oriented along the external electric field. In addition, the energy required for defects to move under an AC electric field is lower than that under a DC electric field. Therefore, the illumination AC polarization method combining illumination and AC electric field can effectively control the defect dipole to be aligned with the domain structure, thereby achieving high polarization quality and mechanical quality factor. Summary of the invention
[0007] In order to solve the above problems, the present application proposes a polarization method and device for improving the mechanical quality factor of ion-doped ferroelectric crystals.
[0008] A polarization method for improving the mechanical quality factor of an ion-doped ferroelectric crystal comprises the following specific steps:
[0009] S1. Electrodes are plated on the surface of the ion-doped ferroelectric crystal and polished to obtain a sample crystal;
[0010] S2. Applying an alternating electric field to the sample crystal for polarization and simultaneously irradiating the sample crystal with a uniform light field to obtain a target crystal, wherein the target crystal is an ion-doped ferroelectric crystal with a high mechanical quality factor.
[0011] Preferably, the ion-doped ferroelectric crystal plane is a (100) plane.
[0012] Preferably, the specific content of polarization by the alternating electric field is:
[0013] The alternating current electric field is a triangular wave alternating current electric field, the intensity of the triangular wave alternating current electric field is in the range of 0.5-1.5 kV / mm, the frequency is in the range of 0.5-5 Hz, and the number of cycles is 20-50.
[0014] Preferably, the wavelength of the uniform light field irradiating the sample crystal is in the range of 400-500 nm and the intensity is 10-50 mW / cm 2 .
[0015] A polarization device for improving the mechanical quality factor of an ion-doped ferroelectric crystal, comprising a laser, an attenuation plate, a spatial optical filter, a convex lens, a sample fixture, and a ferroelectric tester:
[0016] The laser, attenuation plate, spatial light filter and convex lens are aligned in center and placed in sequence;
[0017] One side of the convex lens is a spatial light filter, and the other side is a sample holder, and the sample holder is used to place the sample crystal;
[0018] The ferroelectric tester is arranged outside the sample fixture, and the two ends of the sample crystal are connected to the positive and negative electrodes of the ferroelectric tester.
[0019] Preferably, the laser is used to provide a light source with a wavelength range of 400-500nm;
[0020] The attenuation plate is used to adjust the laser intensity, and the spatial light filter is used to filter and select zero-frequency light to obtain a point light source;
[0021] The convex lens is placed at one focal length of the spatial light filter;
[0022] The light beam emitted by the point light source is expanded into a spatial light field with uniform intensity, and the light intensity is 15mW / cm 2 , the spatial light field with uniform intensity covers the sample crystal.
[0023] Preferably, silicone oil is provided inside the sample fixture, and the silicone oil is used to immerse the sample crystal to prevent the sample crystal from leaking electricity during the AC polarization process;
[0024] The ferroelectric tester is used to apply an alternating electric field to a sample crystal.
[0025] Preferably, the laser light source outputs linearly polarized light, the photon energy of the linearly polarized light exceeds the band gap of the sample crystal, and the relationship between the photon energy of the linearly polarized light and the wavelength is expressed as:
[0026] E = hc / λ;
[0027] Among them, E is the photon energy, h is Planck's constant, c is the speed of light, and λ is the wavelength of light.
[0028] In summary, the polarization method and device for improving the mechanical quality factor of ion-doped ferroelectric crystals of the present invention, compared with the conventional technology, covers the entire crystal with uniform light with energy higher than the band gap of the Mn&Fe:KTN crystal, activates the defect dipoles in the crystal, and promotes the defect dipoles to be oriented along the direction of the polarized AC electric field. After polarization, the defect dipoles inside the Mn&Fe:KTN crystal are aligned with the domain structure, thereby improving the mechanical quality factor of the crystal.
[0029] The technical method of the present invention is further described in detail below through the drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a flow chart of the method for light-induced AC polarization of ion-doped ferroelectric crystals with high mechanical quality factor of the present invention;
[0031] Figure 2 The present invention is a schematic structural diagram of a polarization method and device for improving the mechanical quality factor of an ion-doped ferroelectric crystal.
[0032] Reference numerals
[0033] 1. Laser; 2. Attenuation plate; 3. Spatial light filter; 4. Convex lens; 5. Sample fixture; 6. Sample crystal; 7. Ferroelectric tester. DETAILED DESCRIPTION
[0034] The technical method of the present invention is further described below by means of the accompanying drawings and embodiments. It should be noted that unless otherwise specifically stated, the relative arrangement of the components and steps, numerical expressions and numerical values described in these embodiments do not limit the scope of the present application.
[0035] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the present application, its application, or uses.
[0036] Technologies, systems, and devices known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, systems, and devices should be considered part of the specification.
[0037] In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.
[0038] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0039] Embodiment 1
[0040] The invention provides a polarization method and device for improving the mechanical quality factor of an ion-doped ferroelectric crystal.
[0041] like Figure 1 As shown, a polarization method for improving the mechanical quality factor of an ion-doped ferroelectric crystal includes the following specific steps:
[0042] S1, plating electrodes on the surface of the ion-doped ferroelectric crystal and polishing to obtain a sample crystal 6;
[0043] Furthermore, the ion-doped ferroelectric crystal plane is a (100) plane.
[0044] S2. Apply an alternating electric field to the sample crystal 6 for polarization and simultaneously irradiate the sample crystal 6 with a uniform light field to obtain a target crystal, which is an ion-doped ferroelectric crystal with a high mechanical quality factor.
[0045] The optical field and AC electric field have the advantage of being flexible and adjustable. Electric fields of different frequencies and magnitudes, as well as optical fields of different wavelengths and intensities, can be applied to different types of ion-doped ferroelectric crystals for illumination AC polarization, thereby improving the mechanical quality factor of the crystal. This invention is conducive to the development and application of high-performance new ion-doped ferroelectric crystals.
[0046] Furthermore, the specific content of polarization by the AC electric field is:
[0047] The alternating current electric field is a triangular wave alternating current electric field, the intensity range of the triangular wave alternating current electric field is 0.5-1.5 kV / mm, the frequency range is 0.5-5 Hz, and the number of cycles is 20-50.
[0048] During the AC polarization process, light field irradiation with photon energy higher than the band gap of ion-doped ferroelectric crystals can activate defect dipoles and orient them along the polarization direction. When the defect dipole is oriented in the same direction as the domain structure, the pinning effect provided by the defect dipole can limit the movement of the domain wall and thus improve the mechanical quality factor of the crystal.
[0049] Furthermore, the wavelength of the uniform light field irradiating the sample crystal 6 is in the range of 400-500 nm and the intensity is 10-50 mW / cm 2 .
[0050] Embodiment 2
[0051] like Figure 2 As shown, a polarization device for improving the mechanical quality factor of an ion-doped ferroelectric crystal includes a laser 1, an attenuation plate 2, a spatial optical filter 3, a convex lens 4, a sample fixture 5, and a ferroelectric tester 7:
[0052] The laser 1, the attenuation plate 2, the spatial light filter 3 and the convex lens 4 are aligned in center and placed in sequence;
[0053] One side of the convex lens 4 is a spatial light filter 3, and the other side is a sample holder 5, and the sample holder 5 is used to place a sample crystal 6;
[0054] The ferroelectric tester 7 is arranged outside the sample fixture 5 , and the two ends of the sample crystal 6 are connected to the positive and negative electrodes of the ferroelectric tester 7 .
[0055] Further, the laser 1 is used to provide a light source with a wavelength range of 400-500nm;
[0056] A laser 11 with a wavelength in the range of 400-500 nm is used as a light source, and the output photon energy exceeds the band gap of the sample crystal 6 , ensuring that the photons can be absorbed by the sample crystal 6 .
[0057] The attenuation plate 2 is used to adjust the laser intensity, and the spatial light filter 3 is used to filter and select zero-frequency light to obtain a point light source;
[0058] The laser intensity is adjusted using the attenuation plate 22. The zero-frequency light is filtered and selected using the spatial light filter 33 to obtain a point light source. The convex lens 44 is placed at one focal length behind the spatial light filter 33 to expand the light beam emitted by the point light source into a spatial light field with uniform intensity. The light intensity is 15mW / cm 2, the uniform light field covers the entire sample crystal 6.
[0059] The convex lens 4 is placed at one focal length of the spatial light filter 3;
[0060] The beam emitted by the point light source is expanded into a spatial light field with uniform intensity, and the light intensity is 15mW / cm 2 , a spatial light field with uniform intensity covers the sample crystal.
[0061] Furthermore, silicone oil is provided inside the sample fixture 5, and the silicone oil is used to immerse the sample crystal 6 to prevent the sample crystal 6 from leaking electricity during the AC polarization process;
[0062] The ferroelectric tester 7 is used to apply an alternating electric field to the sample crystal.
[0063] An AC electric field is applied to the sample crystal 6 through a ferroelectric tester 77, with an electric field strength range of 0.5-1.5 kV / mm, a frequency range of 0.5-5 Hz, and a cycle number of 20-50. The AC electric field polarizes the crystal while a uniform light field irradiates the crystal. This method can effectively polarize the crystal within a few minutes.
[0064] Furthermore, the laser light source outputs linearly polarized light, and the photon energy of the linearly polarized light exceeds the band gap of the sample crystal. The relationship between the photon energy of the linearly polarized light and the wavelength is expressed as:
[0065] E = hc / λ;
[0066] Among them, E is the photon energy, h is Planck's constant, c is the speed of light, and λ is the wavelength of light.
[0067] The output photon energy exceeds the band gap of the sample crystal 6 , ensuring that the photon can be absorbed by the sample crystal 6 .
[0068] The photon energy must be greater than the band gap of the sample crystal (2.2eV, corresponding to a wavelength of 558nm). Theoretically, the crystal can absorb laser wavelengths less than 558nm, but it cannot be too small. Too high an absorption rate will cause the crystal temperature to change. The range can be selected to be 400-500nm.
[0069] Embodiment 3
[0070] Taking Mn&Fe:KTN crystal as an example, this application measures the mechanical quality factor of Mn&Fe:KTN crystal after light AC polarization and traditional DC polarization (the ion-doped ferroelectric crystal applicable to this method is theoretically not limited to Mn:Fe:KTN crystal):
[0071] (1) Mn&Fe:KTN crystal with a Curie temperature of 50°C, an AC electric field with a strength of 600 V / mm, a frequency of 1 Hz, and a period of 24, at a wavelength of 491 nm and a strength of 15 mW / cm 2The mechanical quality factor after AC polarization under light field irradiation is 538. The mechanical quality factor of the crystal after traditional DC polarization is 176, and the mechanical quality factor of the AC polarization method is greatly improved by 206%.
[0072] (2) Mn&Fe:KTN crystal with a Curie temperature of 55°C, an AC electric field with a strength of 500 V / mm, a frequency of 2 Hz, and a period of 21, at a wavelength of 410 nm and a strength of 15 mW / cm 2 The mechanical quality factor after AC polarization under light field irradiation is 411. The mechanical quality factor of the crystal after traditional DC polarization is 159, and the mechanical quality factor of the AC polarization method is improved by 158%.
[0073] (3) Mn & Fe: KTN crystal with a Curie temperature of 60°C, an AC electric field with a strength of 800 V / mm, a frequency of 5 Hz, and a period of 21, at a wavelength of 491 nm and a strength of 15 mW / cm 2 The mechanical quality factor after AC polarization under light field irradiation is 525. The mechanical quality factor of the crystal after traditional DC polarization is 186, and the mechanical quality factor of the AC polarization method is improved by 182%.
[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical method of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical method of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical method to deviate from the spirit and scope of the technical method of the present invention.
Claims
1. A polarization method for improving the mechanical quality factor of an ion-doped ferroelectric crystal, characterized in that: The following steps are involved: S1. Electrodes are plated on the surface of the ion-doped ferroelectric crystal and polished to obtain a sample crystal; S2. Applying an alternating electric field to the sample crystal for polarization and simultaneously irradiating the sample crystal with a uniform light field to obtain a target crystal, wherein the target crystal is an ion-doped ferroelectric crystal with a high mechanical quality factor.
2. A polarization method for improving the mechanical quality factor of an ion-doped ferroelectric crystal according to claim 1, characterized in that: The ion-doped ferroelectric crystal plane is a (100) plane.
3. A polarization method for improving the mechanical quality factor of an ion-doped ferroelectric crystal according to claim 1, characterized in that: The specific content of polarization by AC electric field is: The alternating current electric field is a triangular wave alternating current electric field, the intensity of the triangular wave alternating current electric field is in the range of 0.5-1.5 kV / mm, the frequency is in the range of 0.5-5 Hz, and the number of cycles is 20-50.
4. A polarization method for improving the mechanical quality factor of an ion-doped ferroelectric crystal according to claim 1, characterized in that: The wavelength of the uniform light field irradiating the sample crystal is in the range of 400-500nm and the intensity is 10-50mW / cm 2 .
5. A polarization device for improving the mechanical quality factor of an ion-doped ferroelectric crystal, characterized in that: Including laser, attenuator, spatial light filter, convex lens, sample fixture, ferroelectric tester: The laser, attenuation plate, spatial light filter and convex lens are aligned in center and placed in sequence; One side of the convex lens is a spatial light filter, and the other side is a sample holder, and the sample holder is used to place the sample crystal; The ferroelectric tester is arranged outside the sample fixture, and the two ends of the sample crystal are connected to the positive and negative electrodes of the ferroelectric tester.
6. A polarization device for improving the mechanical quality factor of an ion-doped ferroelectric crystal according to claim 5, characterized in that: The laser is used to provide a light source with a wavelength range of 400-500nm; The attenuation plate is used to adjust the laser intensity, and the spatial light filter is used to filter and select zero-frequency light to obtain a point light source; The convex lens is placed at one focal length of the spatial light filter; The light beam emitted by the point light source is expanded into a spatial light field with uniform intensity, and the light intensity is 15mW / cm 2 , the spatial light field with uniform intensity covers the sample crystal.
7. A polarization device for improving the mechanical quality factor of an ion-doped ferroelectric crystal according to claim 5, characterized in that: Silicone oil is arranged inside the sample fixture, and the silicone oil is used to immerse the sample crystal to prevent the sample crystal from leaking electricity during the AC polarization process; The ferroelectric tester is used to apply an alternating electric field to a sample crystal.
8. A polarization device for improving the mechanical quality factor of an ion-doped ferroelectric crystal according to claim 5, characterized in that: The laser light source outputs linearly polarized light. The photon energy of the linearly polarized light exceeds the band gap of the sample crystal. The relationship between the photon energy of the linearly polarized light and the wavelength is expressed as: E = hc / λ; Among them, E is the photon energy, h is Planck's constant, c is the speed of light, and λ is the wavelength of light.